2022
DOI: 10.1186/s13045-022-01352-x
|View full text |Cite
|
Sign up to set email alerts
|

Elraglusib (9-ING-41), a selective small-molecule inhibitor of glycogen synthase kinase-3 beta, reduces expression of immune checkpoint molecules PD-1, TIGIT and LAG-3 and enhances CD8+ T cell cytolytic killing of melanoma cells

Abstract: Background Glycogen synthase kinase-3 (GSK-3) is a serine/threonine kinase with multiple roles in tumour growth, cell invasion and metastasis. We have previously established GSK-3 as an upstream regulator of PD-1 gene expression in CD8 + T cells and demonstrated that GSK-3 inhibition is as effective as anti-PD-1 mAb blockade in controlling tumour growth. Elraglusib (9-ING-41) is a specific small-molecule inhibitor of GSK-3β with clinical activity in patients with advanced cancers, including a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
15
2
Order By: Relevance
“…We also noted that immune cell segments showed differential protein expression based on the proximity to the tumor where tumor-infiltrating immune cells had decreased expression of immune checkpoints (PD-L1, Tim-3, PD-1) and Treg markers (CD25, CD127) as compared to tumor-adjacent immune cells regardless of timepoint. While the downregulation of immune checkpoint proteins PD-1, TIGIT, and LAG-3 by elraglusib has been previously described in melanoma models (47), our findings regarding VISTA and PD-L2 have not yet been reported. These novel observations regarding emerging immune checkpoint inhibitors should be included in future correlative studies regarding GSK-3 inhibition.…”
Section: Discussioncontrasting
confidence: 70%
“…We also noted that immune cell segments showed differential protein expression based on the proximity to the tumor where tumor-infiltrating immune cells had decreased expression of immune checkpoints (PD-L1, Tim-3, PD-1) and Treg markers (CD25, CD127) as compared to tumor-adjacent immune cells regardless of timepoint. While the downregulation of immune checkpoint proteins PD-1, TIGIT, and LAG-3 by elraglusib has been previously described in melanoma models (47), our findings regarding VISTA and PD-L2 have not yet been reported. These novel observations regarding emerging immune checkpoint inhibitors should be included in future correlative studies regarding GSK-3 inhibition.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous articles reported that GSK‐3β inhibition not only disturbed the motion and invasive activity of melanoma cells, but also inhibited the transcription of LAG‐3 and PDCD1 for CD8 + T cells 62,63 . Based on this, the GSK‐3β inhibitor elraglusib enhances the efficacy of anti‐PD‐1 immunotherapy by relieving the exhausted condition of tumor‐specific CD8 + T cells via down‐regulation of PD‐1, LAG‐3, and TIGIT expression 64 . Sustained angiogenesis is one of the most famous hallmarks of cancer.…”
Section: Combination Therapiesmentioning
confidence: 87%
“…62,63 Based on this, the GSK-3β inhibitor elraglusib enhances the efficacy of anti-PD-1 immunotherapy by relieving the exhausted condition of tumor-specific CD8 + T cells via down-regulation of PD-1, LAG-3, and TIGIT expression. 64 Sustained angiogenesis is one of the most famous hallmarks of cancer. Using inhibitors to disrupt the vascular endothelial growth factor (VEGF) signal is a classic cancer treatment strategy.…”
Section: Targeted Therapymentioning
confidence: 99%
“…These findings suggest that GSK3β-inhibition, when used in combination with existing regimen for refractory B-ALL and other lymphoid malignancies, could substantially deepen treatment responses and overcome mechanisms of conventional drug resistance. GSK3β small molecule inhibitors, including LY2090314, AZD1080, Laduviglusib (CHIR99021), Tideglusib and Elraglusib , have demonstrated safety and tolerability at micromolar plasma concentrations (Cmax) [47][48][49][50][51][52][53] . Among the reported adverse effects of LY2090314 in clinical trials (Cmax micromolar) was lymphopenia (Figure S11d), which is consistent with the unique dependency of B-lymphoid cells on GSK3β-mediated degradation of β-catenin discovered in this study.…”
Section: Rationale For Repurposing Of Gsk3β Inhibitors For Refractory...mentioning
confidence: 99%